Nuclear capability, bargaining power, and conflict - LaFleur, Thomas M. (Kansas State University, 2019)
Traditionally, nuclear weapons status enjoyed by nuclear powers was assumed to provide a clear advantage during crisis. However, state-level nuclear capability has previously only included nuclear weapons, limiting this application to a handful of states. Current scholarship lacks a detailed examination of state-level nuclear capability to determine if greater nuclear capabilities lead to conflict success. Ignoring other nuclear capabilities that a state may possess, capabilities that could lead to nuclear weapons development, fails to account for the potential to develop nuclear weapons in the event of bargaining failure and war. In other words, I argue that nuclear capability is more than the possession of nuclear weapons, and that other nuclear technologies such as research and development and nuclear power production must be incorporated in empirical measures of state-level nuclear capabilities. I hypothesize that states with greater nuclear capability hold additional bargaining power in international crises and argue that empirical tests of the effectiveness of nuclear power on crisis bargaining must account for all state-level nuclear capabilities. This study introduces the Nuclear Capabilities Index (NCI), a six-component scale that denotes nuclear capability at the state level. Through an annual, monadic examination of 193 states over 72 years, this study endogenously describes state-level nuclear capability and exogenously compares those results to dyadic conflict depicted in the Militarized Compellent Threat (MCT) and International Crisis Behavior (ICB) datasets, to determine whether a finer examination of nuclear capabilities would yield different results. This study found that higher NCI states, whether challenger or target, are victorious in four of every five conflicts and that higher NCI states are twice as prone to initiate conflict.
Keywords: Nuclear capability; Bargaining power; Conflict; Crisis; Compellent